Entrepreneurial Leadership of Private School Principals in Thailand: The Pathway to School Effectiveness through School Culture and Organizational Citizenship Behavior - Kongjinda, Naritchaya; Niyamabha, Achara; Wichitpatcharaporn, Wisut; Sakulthanasakdi Moore, Kanda; Koedsuwan, Suphot (International Journal of Psychosocial Rehabilitation, 2020)
School effectiveness is one of the key success factors in school. Since the private schools in Thailand today have faced new challenges that affect the capability to compete and have made many private schools struggling to survive, increasing school effectiveness is the prospective solution for schools. School effectiveness today is multi-facet and has been defined in its own context. The school principal is the one who sets the direction and leads the school to success. Entrepreneurial leadership is presented as the character of the leader who will lead the organization to its goal in the time of difficulty and we adopted it to use in a school context, to propel the school effectiveness through school culture and the teacher’s organizational citizenship behavior. The objectives of this study were to study entrepreneurial leadership of the school principals, school culture, teachers’ organizational citizenship behavior, and school effectiveness of private schools in Thailand, and to investigate the structural equation model of school effectiveness for empirical data. Samples of 529 were randomly selected from principals and teachers at private schools. The finding revealed that entrepreneurial leadership of private school principals had no direct effect on school effectiveness but had been mediated by school culture and teacher’s organizational citizenship behavior significantly. Besides, entrepreneurial leadership of administrators, school culture, and organizational citizenship behavior jointly explained 57 percent of the variation in school effectiveness of private schools. The findings and implications of the study are also discussed.